2017
DOI: 10.1111/echo.13643
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic evaluation of patients presenting with acutely decompensated heart failure in the setting of dietary or medication noncompliance—Is there a role?

Abstract: Repeat echocardiograms in patients admitted with HF exacerbation due to noncompliance revealed significant changes in the majority of patients studied. The changes may reflect worsening in cardiac function in addition to the presumed etiology of noncompliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…These abnormalities were less likely to be due to primary valve disease, but rather Importantly, among patients undergoing echocardiography during an admission for AHF, the proportion of those with significant changes over previous echocardiograms is unknown. In a study of 90 patients admitted for AHF with dietary or medication noncompliance as the culprit for decompensation and a previous echocardiogram available, 24 53 (59%) had a repeat echocardiogram performed during index admission; clinically relevant changes could be identified in 63% and 56% of patients with last echocardiogram performed within 1 year or >1 year apart, respectively. The most common changes were >10mmHg increase in right ventricular systolic pressure (RVSP), >10% LVEF decrease, ≥1 grade worsening of mitral regurgitation (MR) or tricuspid regurgitation (TR), new or worsening wall motion abnormalities, new or larger pericardial effusion, and ≥1 grade worsening in diastolic function or right ventricular (RV) systolic function.…”
Section: Main Echocardiographic Findings From Ahf Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These abnormalities were less likely to be due to primary valve disease, but rather Importantly, among patients undergoing echocardiography during an admission for AHF, the proportion of those with significant changes over previous echocardiograms is unknown. In a study of 90 patients admitted for AHF with dietary or medication noncompliance as the culprit for decompensation and a previous echocardiogram available, 24 53 (59%) had a repeat echocardiogram performed during index admission; clinically relevant changes could be identified in 63% and 56% of patients with last echocardiogram performed within 1 year or >1 year apart, respectively. The most common changes were >10mmHg increase in right ventricular systolic pressure (RVSP), >10% LVEF decrease, ≥1 grade worsening of mitral regurgitation (MR) or tricuspid regurgitation (TR), new or worsening wall motion abnormalities, new or larger pericardial effusion, and ≥1 grade worsening in diastolic function or right ventricular (RV) systolic function.…”
Section: Main Echocardiographic Findings From Ahf Studiesmentioning
confidence: 99%
“…The most common changes were >10mmHg increase in right ventricular systolic pressure (RVSP), >10% LVEF decrease, ≥1 grade worsening of mitral regurgitation (MR) or tricuspid regurgitation (TR), new or worsening wall motion abnormalities, new or larger pericardial effusion, and ≥1 grade worsening in diastolic function or right ventricular (RV) systolic function. 24 An echocardiogram at the time of admission for AHF can thus reveal significant changes even in chronic HF cases.…”
Section: Main Echocardiographic Findings From Ahf Studiesmentioning
confidence: 99%
“…While the patient was scheduled for outpatient follow-up for echocardiography after the first admission detailed, the detection of his LV thrombus would remain incidental to the concern of worsening ventricular function. Additionally, only a 42% utilization rate was noted by Goyfman et al with follow-up echocardiogram performed during an index admission for acute decompensated HF in the setting of medication noncompliance where such risk is higher [14]. Irrespective of prophylactic anticoagulation, the unclear risk stratification for thrombus formation in patients with HFrEF may be addressed by evaluating specific cardiac imaging findings (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Current appropriate use guidelines for TTE from the American Heart Association and American Society of Echocardiography suggest that a repeat study be obtained in the setting of a clinical change without a known precipitating cause 6 . TTE even may show structural changes when an apparent trigger for decompensation is identified; one retrospective study found that most patients with a clear history of medication or dietary nonadherence had new findings on a repeat TTE 7 …”
Section: Why You Might Think Routinely Repeating Tte Is Helpful In An...mentioning
confidence: 99%
“…6 TTE even may show structural changes when an apparent trigger for decompensation is identified; one retrospective study found that most patients with a clear history of medication or dietary nonadherence had new findings on a repeat TTE. 7 Recent evidence also suggests that serial TTE during a hospital stay may improve the outcomes of inpatients with ADHF. In a pilot study of 20 patients, researchers enrolled patients with ADHF in a decongestant protocol guided by daily limited TTE assessment of volume status and point-of-care lung ultrasound.…”
Section: Why You Might Think Routinely Repeating Tte Is Helpful In An...mentioning
confidence: 99%